Go green in a greener world: State of the Art in EU&LATAM - Gómez, Andrés; Ponzoa, José Manuel; Mas, José Manuel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The global economy is going through a period of drastic changes. One of the main initiatives is the Green Deal, seeking a modern, resource-efficient competitive economy by 2050. However, transformation implies collaboration by all, not just in Europe but globally. Educate future generations from an ecological perspective, re-qualifying employees within sectors prone to change and modifying or eliminating some jobs in “brown” sectors are some of the causes and consequences of change. Higher Education institutions (HEIs) will be required globally, to provide solutions to the market, providing new professionals able to tackle the New Green Challenge.